Microstructural control during spray deposition processing of liquid immiscible alloys - Anil M.; Ojha S.N. (My University, 2025)
Alloys based on Al-Pb and Cu-Pb systems were gas atomized and spray deposited on a copper substrate. Microstructure of spray deposited Cu-20Pb alloy showed an equiaxed grain morphology of the primary á-phase in contrast to cellular-dendritic morphology of a wide size range of powder particles. A uniform distribution of ultrafine Pb particles was observed in the deposit of Al-4Cu-20Pb alloy against a bimodal size distribution of Pb particles in atomised powder particles of this alloy. The wear rate of Cu-20 Pb alloy was observed to be higher than that of Al-4Cu-20Pb alloy at low load and sliding velocity. However, the former indicated a low wear rate in severe wear regime of high load and sliding velocity. The mode of solidification of liquid immiscible alloys is discussed and their wear behaviour analysed in light of solidification structure of alloys generated during spray deposition processing.